Board characteristics and earnings management in Sri Lanka. Issue 1 (4th September 2019) - Rajeevan, Shanmugavel; Ajward, Roshan
Abstract : Purpose: The purpose of this paper is to examine the association between designated corporate governance attributes and the degree of earnings management in selected quoted companies in Sri Lanka. Design/methodology/approach: In total, 70 listed companies in Colombo Stock Exchange (CSE) were selected based on the highest market capitalisation for the period covering from 2015 to 2017 and representing beverage, food and tobacco, diversified, hotel and travel, manufacturing, oil palms and health care sectors, which accounted for 59.9 per cent of the total market capitalisation of CSE. Findings: This study found a positive relationship between CEO-Chair duality and earnings management. Practical implications: The insights may also provide investors, economic analysts and regulators with early caution indicators of potential problems in a corporation regarding corporate governance failures and aid stakeholders in assessing the effectiveness and efficiency of the board and corporate governance structure and earnings management methods. Originality/value: This study extends the extant research on board characteristics and real earnings management by adopting prominent research design and modernised data. This study offers evidence on how selected audit and board committee's characteristics influence real earnings management practices.